A multicenter retrospective cohort study of blunt traumatic injury to the common or internal carotid arteries. Issue 1 (January 2022) - Jacob-Brassard, Jean; Al-Omran, Mohammed; Haas, Barbara; Nathens, Avery B.; Gomez, David; Dueck, Andrew D.; Forbes, Thomas L.; de Mestral, Charles
Highlights: In this study of blunt carotid injury, 383 patients presented with neurological deficit unrelated to head injury. Invasive intervention of this specific clinical presentation was positively associated with an increase in discharge home. Invasive intervention of this specific clinical presentation was not associated with lower in-hospital mortality. Abstract: Objective: Current EAST guidelines recommend against routine carotid intervention for patients with blunt carotid artery injury (BCI), but offer limited information on its role for BCI patients presenting with neurological deficit. Our goal was to describe the contemporary management and outcomes of patients presenting with BCI and neurological deficit unrelated to head injury. Methods: We identified all adults who sustained a BCI between 2010 and 2017 in the American College of Surgeons Trauma Quality Improvement Program. We extracted patient demographics, injury characteristics (carotid and non-carotid), as well as the frequency, timing and approach of carotid intervention. Presence of neurological deficit unrelated to head injury at presentation was determined using Abbreviated Injury Scale codes. The main outcomes were in-hospital mortality and home discharge. Patients with and without neurological deficit at presentation were compared through multivariable logistic regression modeling. Among those with neurological deficit at presentation, the associations between carotid intervention (open or endovascular) and the outcomes were also assessed through multivariable logistic regression. Results: We identified 5, 788 patients with BCI of whom 383 (7%) presented with neurological deficit unrelated to head injury. Among the 296 patients (5%) who underwent carotid intervention, 36 (12%) had presented with neurological deficit unrelated to head injury. Interventions were most often endovascular (68% [200/296]) and within a median time of 32 h (IQR 5–203). In-hospital mortality was 16% (918/5, 788), and in-hospital stroke prevalence was 6% (336/5, 788). When comparing patients with and without neurological deficit at presentation, those with deficits were more frequently managed with an intervention. After adjustment, the likelihood of mortality was higher (OR [95% CI] = 2.16 [1.63–2.85]) and the likelihood of home discharge lower (OR [95% CI] = 0.29 [0.21–0.40]) among patients presenting with neurological deficit. Among those with neurological deficit, carotid intervention was positively associated with home discharge (OR [95% CI] = 2.96 [1.21–7.23]), but not with in-hospital mortality (OR [95% CI] = 0.87 [0.36–2.10]). Results were similar in the subgroup of patients with isolated BCI (2, 971/5, 788). Conclusions: Intervention in BCI patients presenting with neurological deficit may contribute to a greater likelihood of home discharge but not reduced in-hospital mortality.